Human capital management and decent work: a systematic literature review of mediating mechanisms - Dani Anjar Prihatmanto; Muhammad Ramaditya (Jurnal Konseling dan Pendidikan, 2026)
Public sector organizations increasingly face the challenge of reconciling strategic human capital (HC) management with the imperative of providing decent work. This systematic literature review (SLR) employs the PRISMA 2020 framework to synthesize 42 peer-reviewed studies (2015–2025), exploring the relationships between HC management, Flexible Working Arrangements (FWA), Artificial Intelligence (AI) adoption, Innovative Work Behavior (IWB), and decent work outcomes. Grounded in Human Capital Resources Theory, AMO Theory, and the Psychology of Working Theory, this review addresses a critical gap in the literature: the lack of an integrative model simultaneously testing FWA, AI, and IWB as mediating pathways. Thematic synthesis reveals four overarching findings: HC management serves as the primary strategic antecedent; FWA acts as a critical motivation-enhancer; AI functions as a key ability-enhancer; and IWB serves as the mechanism for opportunity expression. These findings are synthesized into an integrative AMO-based conceptual model, proposing six testable hypotheses for future empirical research. This review contributes to the field by extending AMO Theory to the normative construct of decent work and providing a structured framework for public sector institutions to address systemic workforce deficits. The proposed model offers a roadmap for researchers and policymakers to evaluate how coordinated HC interventions can foster sustainable, decent working conditions in accountability-intensive organizational contexts.